Stent misdeployment and factors associated with failure in endoscopic ultrasound-guided choledochoduodenostomy: analysis of the combined datasets from two randomized trials - Chen, Yen-I; Long, Clara; Sahai, Anand V.; Napoleon, Bertrand; Donatelli, Gianfranco; Kunda, Rastislav; Martel, Myriam; Chan, Shannon M.; Arcidiacono, Paolo G.; Lam, Eric; Kongkam, Pradermchai; Forbes, Nauzer; Larghi, Alberto; Mosko, Jeffrey D.; Van der Merwe, Schalk; Gan, Seng Ian; Jacques, Jeremie; Kenshil, Sana; Ratanachu-Ek, Thawee; Miller, Corey; Saxena, Payal; Desilets, Etienne; Sandha, Gurpal; Alrifae, Yousef; Teoh, Anthony Y. B.; on behalf of the ELEMENT and DRA-MBO working groups; Yassin, Sharif; NG, Kevin K. C.; NG, Enders K. W.; Qatomah, Abdulrahman; Lu, Yidan; Barkun, Alan; Doreen, Alastair; Chiu, Philip W. Y.; Maggio, Davide (Endoscopy, 2024)
Background Stent misdeployment (SMD) is a feared and poorly characterized technical challenge of endoscopic ultrasound (EUS)-guided choledochoduodenostomy (CDS) using lumen-apposing stents. We aimed to ascertain the rate of stent misdeployment in EUS-CDS for malignant distal biliary obstruction (MDBO) and describe its outcomes while identifying variables associated with its occurrence.Method This was a post hoc analysis of two randomized controlled trials comparing EUS-CDS vs. endoscopic retrograde cholangiopancreatography in MDBO. The primary end point was rate of SMD, classified as misdeployment of the distal flange (type I), proximal flange (type II), contralateral bile duct wall injury (type III), or double mucosal puncture (type IV). Multivariable analysis was performed to identify variables associated with SMD and/or technical failure, and with clinical failure or stent dysfunction.Results 152 patients were included. Technical success was 93.4 %. SMD occurred in 11 patients (7.2 %; 95 %CI 3.1 %–11.4 %): 8 type I, 1 type II, and 2 type III. Endoscopic salvage of SMD was successful in 81.8 %. Misdeployment led to adverse events in four patients (two mild, two moderate), giving an overall SMD-related adverse event rate of 2.6 % (95 %CI 0.7 %–6.6 %). On multivariable analysis, extrahepatic bile duct diameter of ≤ 15 mm was associated with increased odds of SMD and/or technical failure.Conclusion SMD was relatively common in EUS-CDS and was associated with an extrahepatic bile duct diameter of ≤ 15 mm. The majority of misdeployments could be rescued endoscopically with low risk for adverse events.